1981
DOI: 10.1007/bf01967616
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in histamine receptors in the vas deferens

Abstract: Histamine, specific H1- and H2-receptor agonists in conjunction with specific H1- and H2-receptor antagonists and other types of classical antagonists were used to characterize histamine receptors in the vasa deferentia of mice, rats and guinea pigs. The H1-receptor mediates contraction while the H2-receptor produces inhibition. There were marked qualitative and quantitative differences in the distribution of the two types of histamine receptors in the vas deferens of different species. Results indicate that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
4
8
0
Order By: Relevance
“…Cimetidine abolished this effect of histamine, thus confirming our previous findings [1,2] that histamine inhibition is mediated by H2-receptors in the preparation. The cyclic nucleotides and phosphodiesterase inhibitors that we tested also produced inhibition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cimetidine abolished this effect of histamine, thus confirming our previous findings [1,2] that histamine inhibition is mediated by H2-receptors in the preparation. The cyclic nucleotides and phosphodiesterase inhibitors that we tested also produced inhibition.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier reports from this laboratory showed that histamine inhibits the contractile response of the mouse vas deferens to electrical field stimulation and to exogenous noradrenaline [ 1,2]. This inhibition is antagonized by cimetidine but not by mepyramine, suggesting that the mouse vas deferens contains a cimetidine-sensitive, inhibitory H2-receptor.…”
Section: Introductionmentioning
confidence: 85%
“…The activation of H 2 receptors by histamine inhibits the muscle contraction response due to a decrease in the Ca 2+ influx necessary for contraction. However, this effect (muscle relaxing) is reduced or totally antagonized by cimetidine [8,42], leading to increased intracellular calcium influx. The excess of calcium ions seems to be one of the main routes involved in the induction of programmed cell death [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has indicated that guinea pig vasa deferentia are endowed with pre‐synaptic inhibitory HA H 3 receptors (Luo et al. 1994) and post‐synaptic excitatory H 1 receptors (Vohra 1981; Tamesue et al. 1998; Smith and Burnstock 2004).…”
Section: Discussionmentioning
confidence: 99%